Dominant Distal Myopathy 3 (MPD3) Caused by a Deletion in the HNRNPA1 Gene. (December 2021) - Hackman, Peter; Rusanen, Salla M.; Johari, Mridul; Vihola, Anna; Jonson, Per Harald; Sarparanta, Jaakko; Donner, Kati; Lahermo, Päivi; Koivunen, Sampo; Luque, Helena; Soininen, Merja; Mahjneh, Ibrahim; et al.
Abstract : Background and Objectives: To determine the genetic cause of the disease in the previously reported family with adult-onset autosomal dominant distal myopathy (myopathy, distal, 3; MPD3). Methods: Continued clinical evaluation including muscle MRI and muscle pathology. A linkage analysis with single nucleotide polymorphism arrays and genome sequencing were used to identify the genetic defect, which was verified by Sanger sequencing. RNA sequencing was used to investigate the transcriptional effects of the identified genetic defect. Results: Small hand muscles (intrinsic, thenar, and hypothenar) were first involved with spread to the lower legs and later proximal muscles. Dystrophic changes with rimmed vacuoles and cytoplasmic inclusions were observed in muscle biopsies at advanced stage. A single nucleotide polymorphism array confirmed the previous microsatellite-based linkage to 8p22-q11 and 12q13-q22. Genome sequencing of three affected family members combined with structural variant calling revealed a small heterozygous deletion of 160 base pairs spanning the second last exon 10 of the heterogeneous nuclear ribonucleoprotein A1 ( HNRNPA1) gene, which is in the linked region on chromosome 12. Segregation of the mutation with the disease was confirmed by Sanger sequencing. RNA sequencing showed that the mutant allele produces a shorter mutant mRNA transcript compared with the wild-type allele. Immunofluorescence studies on muscle biopsies revealed small p62 and larger TDP-43 inclusions. Discussion: A small exon 10 deletion in the gene HNRNPA1 was identified as the cause of MPD3 in this family. The new HNRNPA1-related phenotype, upper limb presenting distal myopathy, was thus confirmed, and the family displays the complexities of gene identification.